Potresni odziv armiranobetonskih sten, povezanih s ploščami brez povezovalnih gred - Janevski, Antonio (Gradbeni vestnik, 2025)
The article investigates the seismic response of reinforced concrete (RC) walls coupled only by slabs, without coupling beams, a configuration often considered as cantilever walls. The study investigates when slabs significantly couple walls to a significant extent and how this affects their overall seismic behaviour. Non-linear pushover and response history analyses revealed coupling level (CL) of up to 50%, particularly in buildings featuring slender walls (aspect ratio > 4), where a significant effective slab width can be activated. A significant CL caused axial forces in the wall piers to vary by up to 80% of the gravity loads, altering changing stiffness and strength, causing pronounced redistributions of seismic demand among wall piers and amplifying shear forces in individual piers by up to 50%. Additionally, the study highlights that, shear demand can also increase due to higher modes of vibration. While the amplification of shear forces due to frame action increased with increasing CL, it was found that shear force amplification due to higher modes was found to decreased. To address the limitations of non-linear pushover analysis in capturing higher-mode effects, simple correction expressions are proposed, with deviations in most cases under below 20%.
Keywords: AB-stene; coupling level; frame action; higher mode effects; nelinearna analiza; non-linear analysis; okvirni učinek; potresni odziv; povečanje strižnih sil; RC walls; seismic response; shear amplification; stopnja povezanosti; vpliv višjih nihajnih oblik